2001
DOI: 10.1046/j.1528-1157.42.s6.1.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Changes After Surgical Treatment for Temporal Lobe Epilepsy

Abstract: Summary:   Purpose: The effect of unilateral temporal lobectomy on seizure frequency is well recognized, but little is known about the neuropsychological changes that occur after surgical treatment. We assessed neuropsychological status in 26 patients with an average age of 35 years before and after unilateral temporal lobectomy for medically intractable TLE. Methods: Neuropsychological examination to assess cognitive function, memory, attention, visuospatial analysis, language, and emotional functions was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
2
14
0
1
Order By: Relevance
“…A comparative trial that examines the outcomes of anterior temporal lobectomy against selective temporal resections for both epilepsy and nonepilepsy patients should be considered. As some patients have postoperative improvements in cognitive function after surgeries using the lateral approach or transsylvian approach (23,31), other factors besides the BTLA contribute to postoperative improvement in verbal memory. Preservation of part of the amygdaloid body and fiber tract, such as the anterior temporal stem, as well as trajectories of cholinergic pathways from the nucleus basalis of Meynert and uncal fiber, may also lead to better neuropsychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparative trial that examines the outcomes of anterior temporal lobectomy against selective temporal resections for both epilepsy and nonepilepsy patients should be considered. As some patients have postoperative improvements in cognitive function after surgeries using the lateral approach or transsylvian approach (23,31), other factors besides the BTLA contribute to postoperative improvement in verbal memory. Preservation of part of the amygdaloid body and fiber tract, such as the anterior temporal stem, as well as trajectories of cholinergic pathways from the nucleus basalis of Meynert and uncal fiber, may also lead to better neuropsychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is controversial whether seizure control is correlated with postoperative verbal memory (31) or not (22). Sparing the BTLA preserves this memory function but does not improve it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Luria's theories, after a cortical lesion in the brain, the brain can compensate by distributing the specific function to other areas,1 , 2 particularly in children,11 as observed elsewhere 42. Potentially corroborating data may be, for example, which type of surgery for temporal lobe epilepsy improves neuropsychological test scores for the same patients, particularly those experiencing a reduction in seizures 51…”
Section: Discussionmentioning
confidence: 97%
“… 12 In contrast, other VNS studies found no significant changes in depression, whereas significant improvements were observed on anxiety scales or QOL after VNS implantation. 13 14 While many studies have investigated the QOL in epilepsy patients who underwent resective surgery, 15 16 17 18 only a few studies have evaluated QOL changes in patients receiving VNS treatment. 14 19 20 21 Two studies found significant improvements in QOL at follow-ups after 12 months in 19 patients 20 and 3–12 months in 56 patients.…”
Section: Introductionmentioning
confidence: 99%